CFD Investigation of Pollutant Emission in Can-Type Combustor Firing Natural Gas, LNG and Syngas - Hasini H.; Fadhil S.S.A.; Mat Zian N.; Om N. (Institute of Physics Publishing, 2023)
Carbon dioxide; Combustion; Combustors; Gas turbines; Gases; Liquefied natural gas; Natural gas; Pollution; Synthesis gas; Thermoelectric power plants; Appropriate models; Combustion pro-cess; Numerical calculation; Pollutant emission; Pollutant species; Reduction of co; Syngas combustion; Thermal power plants; Computational fluid dynamics; carbon dioxide; chemical composition; chemical pollutant; combustion; computational fluid dynamics; concentration (composition); emission; liquefied natural gas; machinery; nitrogen oxides; numerical method; power plant; prediction; software; turbine